PENGARUH PEMBERIAN PUPUK ROCK PHOSPHATE TERHADAP PRODUKSI TANDAN BUAH SEGAR (TBS) KELAPA SAWIT (Elaeis guineensis. Jacq) - Muhamad Rizal (Universitas Lancang Kuning, 2017)
This study aimed to determine the effect of rock phosphate fertilizer with various doses of the production of oil palm fresh fruit bunches. Results from this study is the final conclusion of phosphate rock fertilizer does not affect the measurement of the diameterbuah fresh, fresh fruit weight and number brondolan fall and was advised to continue observation until 6 months after treatment applications in order to look the influence of rock phosphate. Rock Phosphate Fertilizers no real effect on the diameter of oil palm fresh fruit bunches in the cultivation of oil palm trees suggested in this study a longer observation that 6 months.